Caulis spatholobi residue fiber reinforced biodegradable poly (propylene carbonate) composites: The effect of fiber content on mechanical and morphological properties. Issue 2 (10th September 2013) - Chen, Fuquan; Liu, Huanyu; Zhao, Yongqing; Feng, Yanhong; Guo, Ruibiao; Wu, Zhenghuan; Chen, Huizhuo; Tang, Hailong; Qu, Jinping
<x xml:space="preserve">Abstract</x> Adding caulis spatholobi residue fiber (CSRF) to reinforce biodegradable poly (propylene carbonate) (PPC) as a reinforcement was investigated. The morphology of CSRF before and after continuous steam explosion, the mechanical and morphological properties of PPC/CSRF bio‐composites with different fiber content were investigated using scanning electron microscopy (SEM), mechanical tests and infrared spectroscopy. The tensile strength and modulus, and impact strength of the bio‐composites increased as the content of fiber increased in composites, the elongation at break declined. It was found that a small stay‐segment in the stress–strain curves and pulled‐out fibers on fractured surfaces of the composites. Infrared spectra result showed esterification and formation of hydrogen bonds between the matrix and CSRF. The fractured surface of the composites addressed a promotion of the interfacial interactions. POLYM. COMPOS., 35:208–216, 2014. © 2013 Society of Plastics Engineers